Food fraud - Ryan, John M. (Academic Press, 2016)
"Food Fraud provides an overview of the current state on the topic to help readers understand which products are being impacted, how pervasive food fraud is, and what laws are in effect across the developed world. This book is an essential quick reference that will familiarize readers with the latest issues surrounding the food industry"--Provided by publisher.